2007
DOI: 10.1002/ptr.2001
|View full text |Cite
|
Sign up to set email alerts
|

Screening of some medicinal plants from cameroon for β‐Lactamase inhibitory activity

Abstract: In efforts to find new bioactive beta-lactamase inhibitors, this study investigated 16 Cameroonian plants belonging to 10 families which were evaluated for anti-beta-lactamase activity. The investigation showed that extracts 2, 6, 3 and 5 of the 16 plants investigated presented interesting in vitro beta-lactamase inhibition (over 90%), respectively, of the beta-lactamases TEM-1, OXA-10, IMP-1 and P99. These extracts were from Mammea africana (all beta-lactamases), Garcinia lucida, G. kola (OXA-10, IMP-1 and P9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…It is probable that some of these compounds, alone or in combination, are responsible for the observed antimicrobial properties as previously shown. In addition, previous studies showed that most of these plant extracts are beta-lactamase inhibitors [11]; therefore, active plant extracts had not only antimicrobial properties, but also anti-beta-lactamase activities. Moreover, some of the plant extracts showed good antifungal activities on yeast (D. picta), filamentous fungi (G. kola, G. lucida, B. micrantha) and all fungi (P. africana) (results not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is probable that some of these compounds, alone or in combination, are responsible for the observed antimicrobial properties as previously shown. In addition, previous studies showed that most of these plant extracts are beta-lactamase inhibitors [11]; therefore, active plant extracts had not only antimicrobial properties, but also anti-beta-lactamase activities. Moreover, some of the plant extracts showed good antifungal activities on yeast (D. picta), filamentous fungi (G. kola, G. lucida, B. micrantha) and all fungi (P. africana) (results not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In an ongoing programme of research and development of traditional medicine in Cameroon focused on the screening of traditionally used Cameroonian plants for antimicrobial properties, we have reported antibacterial activities on Gram positive bacteria [10], and beta-lactamase inhibitory properties of some plant extracts [11]. The present study was initiated to evaluate the antimicrobial activity of 17 crude extracts from 12 medicinal plants against beta-lactam-resistant bacteria.…”
Section: Introductionmentioning
confidence: 98%
“…These probably also explain its reported aphrodisiac properties. In their efforts to find new bioactive β-lactamase inhibitors, Gangoué-Piéboji et al (2007; investigated 16 Cameroonian plants and found that, extracts from G. lucida, together with other species, presented interesting in vitro β-lactamase inhibition. The isolation and the structural elucidation of the active constituents of G. lucida could provide useful leads in the development of β-lactamase inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…There are four main mechanisms used by bacteria to resist beta-1actamines molecules: i) enzymatic inactivation, ii) the modification of the cellular target of the antibacterial agent, iii) the cellular efflux and, iv) the decrease or absence of penetration of the antibiotic in the bacteria. The combination of these mechanisms in a bacterium makes its multi-resistant to many antibiotics (Gangoue-Piéboji et al, 2004). Similarly, several cases of fungi resistant to conventional antifungal agents have been reported.…”
Section: Introductionmentioning
confidence: 99%